A Competency-Based Human Resource Development for Salafiyah Islamic Boarding School Teachers in The Riau Islands - Hantoro, Ramandha Rudwi; Yamin, Martinis; Rosadi, Kemas Imron (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2024)
This study aims to develop a competency-based human resource development system for teachers at Salafiyah Islamic boarding schools in the Riau Islands. It employs Research and Development (R&D) with a Design-Based Research (DBR) approach, adapting the Martin Tessmer model, which includes stages such as preliminary study, product design and expert validation, and product trials. The research uses qualitative data, collected through questionnaires assessing the validity and development of competencies for Islamic boarding school teachers. The study finds that Salafiyah Islamic boarding schools in the Riau Islands currently lack a systematic and sustainable competency development system for their teachers. The validity of the Salafiyah Islamic Boarding School Teacher Competency Development product was assessed by education, language, and Islamic education experts. The material experts rated the product with an average score of 96%, indicating it is very valid. Language experts gave it a score of 72%, which is considered valid. Media experts rated it with an average score of 92%, also classified as valid. The results of the test showed good results through three stages of trials, namely one-to-one, small group, and field test, each of which obtained a percentage value of 82%, 87% and 90% in the very good category. This proves that the product produced is suitable for use by pesantren.